Investigation of the Internal Solitary Wave Influence on Subsea Equipment Lowering with a Continuous Lowering Analysis Model - Mingjie Li; Junliang Zhang; Guosong Chen; Mengjie He; Pan Gao (Journal of Marine Science and Engineering, 2025)
Deep-water payload lowering operations are highly sensitive to hydrodynamic disturbances, particularly to internal solitary waves (ISWs) that are frequently observed in the South China Sea and other stratified shelf regions. This study develops a two-dimensional lumped-mass cable-payload model to investigate the dynamic responses of a lowering system subjected to combined excitations of vessel heave, uniform background current, and ISW-induced velocity shear. With the variable-domain technique, the model incorporates variable boundary conditions through element activation, Morison-type hydrodynamic loading, and a simplified but physically consistent mode-1 ISW kinematic representation based on an extended KdV formulation with vertical modal decay. Numerical implementation is achieved using an explicit central-difference scheme with initialization through static equilibrium and ramped velocity conditions. Parametric simulations are performed to examine the coupled influence of ISW peak velocity, heave amplitude, and lowering speed on cable tension and lateral displacement. Results indicate that ISWs can significantly amplify dynamic loads. The continuous lowering analysis model provides a valuable tool for subsea equipment lowering simulation. And the findings provide quantitative evidence of ISW-induced risks in deep-water lowering.